2012
DOI: 10.1029/2011ja017263
|View full text |Cite
|
Sign up to set email alerts
|

Reconnection at the magnetopause of Saturn: Perspective from FTE occurrence and magnetosphere size

Abstract: Flux transfer events observed at Mercury, Earth, and Jupiter are attributed to spatially and temporally limited events in which the magnetosheath and magnetospheric magnetic field become interconnected and magnetic flux is transported from the dayside to the lobes of the magnetotail. Examination of the Saturnian magnetopause at local times from 1000 to 1400 shows no evidence for this phenomenon. Nevertheless, we do find brief intervals during which the normal component of the magnetic field across the magnetop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 33 publications
1
65
1
Order By: Relevance
“…An investigation of Cassini measurements in Saturn's magnetosheath by Masters et al (2014) found that in this case there is no difference in the plasma depletion layer for northward and southward IMF, which is contrary to the results of related Voyager measurements that indicated an IMF effect (Violante et al, 1995). Masters et al (2014) inferred that reconnection at the dayside magnetopause is not effective at Saturn. We emphasize that this may concern only northward IMF conditions, but not necessarily southward IMF conditions.…”
Section: Southward and Northward Imfcontrasting
confidence: 45%
See 4 more Smart Citations
“…An investigation of Cassini measurements in Saturn's magnetosheath by Masters et al (2014) found that in this case there is no difference in the plasma depletion layer for northward and southward IMF, which is contrary to the results of related Voyager measurements that indicated an IMF effect (Violante et al, 1995). Masters et al (2014) inferred that reconnection at the dayside magnetopause is not effective at Saturn. We emphasize that this may concern only northward IMF conditions, but not necessarily southward IMF conditions.…”
Section: Southward and Northward Imfcontrasting
confidence: 45%
“…The magnetic flux transport rate due to reconnection in this case appears to be lower than the rate of magnetic flux advection due to the solar wind flow. This may imply that conditions for magnetopause reconnection are less favorable at Saturn compared to those at the Earth (Masters et al, 2014).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations